2020
DOI: 10.3389/fphar.2020.00715
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Enlarged Perivascular Spaces and Cognitive Function: A Meta-Analysis of Observational Studies

Abstract: Enlarged perivascular spaces (ePVS), visible on magnetic resonance imaging (MRI), are associated with aortic pulse wave changes produced by arterial stiffening. However, the relationship between ePVS and cognition is still unclear. We aimed to benchmark current knowledge of associations between ePVS and cognitive function using a meta-analysis of all available published data. We searched three databases for studies examining ePVS and cognition, identified seven studies involving 7,816 participants, plotted mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
0
15
1
Order By: Relevance
“… 38 The incidence of cognitive impairment in patients with large numbers of BG-EPVSs is not clear, research on the relationship between large numbers of BG-EPVSs and cognitive impairment insufficient, and results have not been consistent. 14 , 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 38 The incidence of cognitive impairment in patients with large numbers of BG-EPVSs is not clear, research on the relationship between large numbers of BG-EPVSs and cognitive impairment insufficient, and results have not been consistent. 14 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…Several BG-EPVSs are generally considered clinically silent. Recent studies have shown a relationship between EPVSs and cognitive disturbances; 14 , 15 but others have found EPVSs not to be related to cognitive impairment. 16 Therefore, the association between EPVSs and cognitive impairment is attributed to a direct effect of EPVSs or accompanying CSVD markers, eg, white-matter hyperintensity (WMH), cerebral microbleeds (CMBs), and lacunae, and remains incompletely understood.…”
Section: Introductionmentioning
confidence: 98%
“…More recent cross-sectional evidence demonstrates an increase in ePVS with age and vascular risk factors, including WMH volume, suggesting ePVS may be a marker of cSVD (18,(20)(21)(22)(23)(24)(25). Accumulating evidence also suggests a negative association between ePVS and cognitive processes including executive function, processing speed, semantic memory, and visuospatial ability (26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…However, the consequences of BG-EPVS are largely unknown. Although they are generally considered clinically silent, some studies explored the association between EPVS and cognitive disturbances ( Zhu et al, 2010 ; Jie et al, 2020 ). However, the results were not consistent across the studies.…”
Section: Introductionmentioning
confidence: 99%